Some Social Characteristics of CEGEP Graduates' - Dennis, Ann B. (Canadian Journal of Higher Education, 1975)
As part of the "Quiet Revolution" in Quebec in the 1960's, changes have occurred both in the educational structures and in the population undertaking post-secondary studies. A new post-secondary institution, the CEGEP, has been introduced. As a preliminary step in the study of accessibility to the CEGEP, the social class, ethnicity and sex of its graduates are related to their course of study at CEGEP and their subsequent work or educational activi- ties. There were no clear-cut patterns of ethnic or social class differences in choice of specialisation. Although field of specialisation remained strongly sex-linked, women constitu- ted a significant proportion of the graduates. Social classes continued to be distributed inequitably in the student population, although the disparities varied with ethnicity, being least in the case of those whose origins were neither English nor French. The pre-university programme, as intended, wax being treated as part of a cycle of post-secondary education, and suitable employment for graduates of the terminal, vocational programmes was not a problem.